Autoinflammatory Reaction in Dogs Treated for Cancer via G6PD Inhibition - Jonathan W. Nyce (Case Reports in Veterinary Medicine)
Glucose-6-phosphate dehydrogenase (G6PD) is an oncoprotein that is overexpressed in cancer cells to provide the NADPH required for their increased anabolism. NADPH, sourced from G6PD fuels nucleotide biosynthesis, maintains redox potential of thioredoxin and glutathione and drives the mevalonate pathway that powers many of the basic mechanisms by which cancer cells escape host control. G6PD is thus a target for cancer treatment being addressed by many groups around the world. We have discovered that systemic inhibition of G6PD by high dose dehydroepiandrosterone (DHEA) causes a severe autoinflammatory response in dogs, which does not occur in mice or rats. Since dogs more closely model the human adrenal androgen system than do common laboratory animals, this finding is relevant to the design of G6PD-inhibiting drugs for humans. The autoinflammatory reaction observed closely resembles mevalonate kinase deficiency (MKD), a rare autosomal recessive disease in humans characterized by recurrent febrile attacks, arthralgia, skin rash, and aphthous ulcers of mucocutaneous tissues. In a manner comparable to animal models of MKD, the reconstitution of protein geranylgeranylation blocked the autoinflammatory reaction caused by systemic G6PD inhibition. This autoinflammatory response to systemic G6PD inhibition represents an unexpected result that must be taken into consideration when targeting this oncoprotein.